Secukinumab treatment in a pediatric patient with corticosteroid-intolerant pyoderma gangrenosum: a case report - Liwei, Wang; Yihong, Qian; Fei, Tan; Chao, Yuan (Frontiers in Medicine, 2025)
Pyoderma gangrenosum (PG) is a rare, rapidly progressive, non-infectious neutrophilic dermatosis characterized by severely painful ulcers. Its pathogenesis may be attributed to genetic factors, autoimmune dysfunction, and neutrophil disorders. Interleukin-17 (IL-17) inhibitors can suppress neutrophil activity by blocking the IL-17/IL-23 axis, which has been documented to be effective in PG treatment. However, there is limited response rate of treatments with the use of IL-17 inhibitors for PG. Accordingly, the present study reports on a pediatric case of corticosteroid-intolerant pyoderma gangrenosum treated with the IL-17A inhibitor secukinumab, where the patient achieved significant improvement. This case underscores that secukinumab may be a promising therapeutic option for pediatric PG, offering valuable insights for clinical practice in managing such refractory cases.